Targeting key players in lipid biosynthesis for NAFLD and NASH treatment: Lipid biosynthesis and NAFLD treatment - Siapoush, Samaneh; Milani, Morteza; Zarghami, Nosratollah; Ebrahimi-kalan, Abbas; Rezaei, Ramazan; Rahmati, Mohammad (Cellular and Molecular Biology, 2024)
Undoubtedly, nonalcoholic fatty liver disease (NAFLD) is widely recognized as one of the most prevalent liver diseases worldwide, encompassing a broad spectrum from simple steatosis to the most advanced stage of nonalcoholic steatohepatitis (NASH). However, effective treatments for NAFLD and NASH have not yet been clearly defined. Using appropriate terms such as "Nonalcoholic Fatty Liver Disease", "NAFLD treatment", “Lipid metabolism”, “lipid biosynthesis”, autophagy “bFGF” and TFG-b” apoptosis, we searched for relevant articles in the PubMed and Scopus databases. This review will discuss the role of the most important players in controlling lipid biosynthesis and lipid metabolism imperfection, which leads to NASH and NAFLD. Furthermore, potential pharmacological agents for targeting molecules and signaling pathways involved in liver inflammation, fibrosis, and cell death are also discussed.